(untitled) (Research, Society and Development, 2022)
In the past few decades, droughts have increased along with the globe, including in Brazil, and such episodes occur with greater severity in the Brazilian Northeast (NEB). Consequently, these droughts trigger environmental, socio-economic, and regional problems. This work assessed the behavior of these events from Vegetation Health Index (VHI) on the NEB. This analysis will be carried out from the Global Vegetation Health (GVH) data, based on the satellite records via Advanced Very High-Resolution Radiometer (AVHRR) sensor, made available by National Oceanographic and Atmospheric Administration (NOAA). These data have temporal resolution on a weekly scale during the years 1982-2019, to which they were converted to annual composites, while the spatial resolution is 4km x 4km. A prior analysis was realized and selected 1983, 1993, 1998 (three episodes of El Niño), and 2012 (anomalous episode of La Niña), based on the Oceanic Niño Index (ONI). The results obtained from the annual VHI behavior pointed out significant spatial differences, with the classes referring to severe drought (annual VHI between 0-6%) and extreme (annual VHI between 6-12%) detected in the states of Ceará, Piauí, and Rio Grande do Norte during the years 1983, 1993 and 2012. The year 2012 was the most severe among the years analyzed, with the highest percentage of the class regarding extreme and severe drought with the values of 0.5% and 5.5% of the total area of the NEB, respectively, mainly in the central region of Bahia. The drought initiated during the La Niña of 2012 lasted until 2017 caused a devastating effect on the NEB, causing substantial variability in the rainfall totals, culminating in enormous socio-environmental and economic damage.